2017
DOI: 10.23956/ijarcsse/v7i6/0148
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on Agriculture Ontology: A Global Perspective

Abstract: Abstract-Ontologies have played a vital role in the field of agriculture. The agriculture domain is a vast and complex system science and the knowledge of it consists of many concepts and relationships. These difficult concepts and relationships have been modelled using Ontologies in various capacities in different countries. This paper is an exploratory study, presenting a review on the various ontology-based applications developed specifically in the domain of agriculture. It also discusses the various Agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Agricultural ontologies seek to solve such incompatibilities by establishing a shared vocabulary across different datasets, permitting easier aggregation, comparison, and analysis while ensuring that data are machine readable and interoperable across platforms (Baker et al, 2019). There are a few widely accepted agri-food ontologies already in existence, and many more under development (Arnaud et al, 2020; Jebaraj and Sathiaseelan, 2017). Some ontologies map crop-specific breeding traits, such as the Oat Ontology developed by the public–private research partnership Oat Global at the University of Minnesota; some are geographically anchored, such as the nationally oriented ontologies developed by the Agriculture Ontology Service Research Group in the Chinese Academy of Agriculture Sciences; while others catalog agronomic practices and techniques, such as CGIAR’s Agronomy Ontology (AgrO).…”
Section: Open Data For Agricultural Development: Elements Of Data Col...mentioning
confidence: 99%
“…Agricultural ontologies seek to solve such incompatibilities by establishing a shared vocabulary across different datasets, permitting easier aggregation, comparison, and analysis while ensuring that data are machine readable and interoperable across platforms (Baker et al, 2019). There are a few widely accepted agri-food ontologies already in existence, and many more under development (Arnaud et al, 2020; Jebaraj and Sathiaseelan, 2017). Some ontologies map crop-specific breeding traits, such as the Oat Ontology developed by the public–private research partnership Oat Global at the University of Minnesota; some are geographically anchored, such as the nationally oriented ontologies developed by the Agriculture Ontology Service Research Group in the Chinese Academy of Agriculture Sciences; while others catalog agronomic practices and techniques, such as CGIAR’s Agronomy Ontology (AgrO).…”
Section: Open Data For Agricultural Development: Elements Of Data Col...mentioning
confidence: 99%
“…This is witnessed in recent reviews of the use of semantic technologies in agriculture (Jebaraj & Sathiaseelan, 2017;Drury et al, 2019) and a recent review and evaluation of existing agricultural ontologies (Goldstein et al, 2019). Many studies have specifically reported on the use of ontologies in agriculture (Hu et al, 2011;Kim et al, 2013;Dineshkumar et al, 2014;Harika & Bhargav, 2015;Sivamani et al, 2016;Jebaraj & Sathiaseelan, 2017;Ngo et al, 2018;Goldstein et al, 2019;Nidhi et al, 2021;Jachimczyk et al, 2021) and climate change (Diop & Lo, 2013;Pileggi & Lamia, 2020) domains. Kim et al (2013), Harika and Bhargav (2015) and Sivamani et al (2016) developed context aware ontologies for seamless services access in vertical farming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the semantic modelling of agriculture has attracted researchers in recent years (Ramar & Gurunathan, 2017;Jebaraj & Sathiaseelan, 2017;Goldstein et al, 2019;Drury et al, 2019;Kessler et al, 2021;Roussey et al, 2021;Abayomi-Alli et al, 2021) and has resulted in the development of ontologies for agriculture (Hu et al, 2011;Kim et al, 2013;Jebaraj & Sathiaseelan, 2017;Ngo et al, 2018;Arnaud et al, 2020;Jachimczyk et al, 2021;Nidhi et al, 2021), no research to date has focused on building a knowledge base ontology for the CSA domain. This study attempts to fill this gap through the development of a Climate Smart Agriculture Ontology (OntoCSA).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have developed different models in order to explain the farming behavior (Dury et al, 2012;Jones et al, 2017a). According to the common ground of these models, the fivestage farming decision process includes (a) the domain recognition, (b) product characterization, (c) farm management, (d) limiting factors control, and (e) post-production evaluation (Antle et al, 2017;Kyaruzi et al, 2019;Jebaraj & Sathiaseelan, 2017). Figure 1 depicts the framework for FAABB as advocated in literature (Kyaruzi et al, 2019b).…”
Section: Farming As a Business Stagesmentioning
confidence: 99%
“…These difficult concepts and relationships have been modelled using Ontologies in various capacities in different countries. A review of the various ontology-based applications developed specifically for the domain of agriculture is presented by Jebaraj and Sathiaseelan (2017). The authors in this work also discuss various agriculture ontologies created by specific developing countries.…”
Section: Agricultural Ontology Generator Componentmentioning
confidence: 99%